2020
DOI: 10.3389/fmicb.2020.607735
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Lactobacillus rhamnosus GG Promotes Mouse Gut Microbiota Diversity and T Cell Differentiation

Abstract: Lactic acid bacteria (LAB) are the primary genera of the intestinal flora and have many probiotic functions. In the present study, Lactobacillus rhamnosus GG (LGG) ATCC 53103 was used to treat BALB/c mice. After LGG intervention, both low and high LGG doses were shown to improve the observed OTU, Chao1, ACE, and Shannon indices, while the Simpson index decreased, demonstrating that LGG can promote intestinal microbiota abundance and diversity. Furthermore, LGG treatment increased the abundances of intestinal F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…Most clinical trials employing probiotics focus on clinical outcomes but lack quantitative microbiome data. However, LGG has been associated with changes in microbiota composition in mouse studies, 25 26 and human studies of other Lactobacillus spp have demonstrated that probiotic administration significantly alters the gut microbiota 27 28 ; therefore, further studies such as ours are needed to elucidate its effects of LGG specifically on the human microbiome. In the interest of social distancing, we are employing a novel approach to conduct the study entirely remotely; this also allows us to recruit participants nationally across the USA.…”
Section: Introductionmentioning
confidence: 95%
“…Most clinical trials employing probiotics focus on clinical outcomes but lack quantitative microbiome data. However, LGG has been associated with changes in microbiota composition in mouse studies, 25 26 and human studies of other Lactobacillus spp have demonstrated that probiotic administration significantly alters the gut microbiota 27 28 ; therefore, further studies such as ours are needed to elucidate its effects of LGG specifically on the human microbiome. In the interest of social distancing, we are employing a novel approach to conduct the study entirely remotely; this also allows us to recruit participants nationally across the USA.…”
Section: Introductionmentioning
confidence: 95%
“…Inoculating commensal bacteria into mice allows to study how bacteria influence the gut microbiota and host immunity in vivo (21)(22)(23). In vitro human peripheral blood mononuclear cells (PBMCs) and intestinal epithelial cells are widely used to evaluate the anti-/proinflammatory potential of bacteria in humans (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…LGG has been previously shown to increase the percentage of the TH17 cells when co-cultured with human PBMCs ( 48 ). Also, a higher percentage of the TH17 cells was observed in the spleens of LGG groups when compared to that of the control groups in Shi et al's study ( 49 ). In contrast, the probiotic strains, Enterococcus faecalis FK-23 and Bifidobacterium infantis , have been associated with a reduced TH17-immune-response in different animal models ( 50 , 51 ).…”
Section: Discussionmentioning
confidence: 73%